New Screening System Using Forward-Viewing Radial Endoscopic Ultrasound and Magnetic Resonance Imaging for High-Risk Individuals With Familial History of Pancreatic Cancer - Ashida, Reiko; Ioka, Tatsuya; Takada, Ryoji; Fukutake, Nobuyasu; Ikezawa, Kenji; Ohkawa, Kazuyoshi; Nagata, Shigenori; Takahashi, Hidenori (Frontiers in Medicine, 2022)
Background and aims: Attention is increasingly being paid to family history of pancreatic cancer (PC) as a risk factor for developing PC. It is mandatory to develop a screening system for early detection of PC; however, the relationship between a family history of PC and incidence of pancreatic abnormalities such as pancreatic cyst and chronic pancreatitis (CP) in the Japanese population remain unknown. Patients and methods: Individuals with a family history of PC were prospectively enrolled in a screening program using forward-viewing radial EUS (FR-EUS) and MRI with MRCP as the diagnostic modalities. Results: Forty-three individuals in 37 families were enrolled (mean age, 54 years). All individuals underwent FR-EUS and MRI with no complications. FR-EUS revealed resectable PC (n=1, 2.3%), pancreatic cysts (n=24, 55.8%), IPMN (n=13, 30.2%), and early CP-like appearance (n=15, 34.9%). The detection rate of early CP-like appearance was significantly higher by EUS than by MRI. Pancreatic cysts and IPMN detected by FR-EUS were significantly correlated to age (≥60 years) and less correlated to male (hazard ratio [HR] 22.4; 95%CI,　2.10–236.0; p<0.01 and HR 0.092; 95%CI, 0.01–0.83; p=0.033, respectively). Early CP-like appearance detected by FR-EUS was significantly correlated with male and smoking (HR 5.0; 95%CI, 1.3–19.3; p=0.02 and HR 4.02; 95%CI, 0.991–16.3; p=0.05, respectively). Conclusions: A screening system using FR-EUS and MRI/MRCP for individuals with a family history of PC was useful for identifying curable PC and pancreatic abnormalities. The incidence of pancreatic cyst including IPMN and early CP-like appearance was also high in Japanese cohort.